Effects of arbuscular mycorrhizal inoculants and phosphate fertilizer on growth and nutrient uptake of aerobic rice (Oryza sativa L. var MR1A) / Rosina Baadu - Baadu, Rosina (2019)
Malaysia introduced aerobic rice varieties to combat water-scarce conditions under the Tenth plan Malaysia plan (2011-2015). However, its sustainability has been jeopardized by lower average yield production, which requires an effective and costeffective nutrient management strategy. Recent studies focused on the significance of phosphate (P) in the interaction of plants and arbuscular mycorrhizal fungi (AMF) as biofertilizer in the rice agricultural industry's development. Therefore, a pot culture experiment was carried out to evaluate the effect of different mycorrhiza inoculants and phosphate application on the growth of aerobic rice, Oryza sativa L. var. MR1 A. Three different treatments of mycorrhiza applied were Glomus mosseae (GM), commercial mycorrhiza (CM) and co-inoculation of both types. Two phosphorus application levels of 0 and 300 mg kg"1 were added to investigate the influence of inoculations on the nutrient uptake by the plant. All the treatments were designed as completely randomized design. The results showed a significant effect of coinoculation of Glomus mosseae and commercial mycorrhizal in presence of P fertilizer on plant height (135.85±9.63 cm), number of tillers (17.75±1.50 nos), P uptake by shoots (0.24±0.01%) and percentage of AM root colonization (56.56±1.29%) compared to other treatments. The results indicated that AMF had increased the efficiency of phosphate fertilizer uptake by the plant. This is due to the ability of MR1A seedlings in forming a symbiotic relationship with AM fungi inoculums (G. mosseae, commercial mycorrhizal and co-inoculation of G mosseae and commercial mycorrhizal).